Serotonin modifies the impact of sleep disturbance on suicidality in patients with acute coronary syndrome - Kim, Jae-Min; Kim, Ju-Wan; Kang, Hee-Ju; Choi, Wonsuk; Ryu, Seunghyong; Lee, Ju-Yeon; Kim, Sung-Wan; Kim, Jung-Chul; Chun, Byung Jo; Shin, Il-Seon; Ahn, Youngkeun; Jeong, Myung Ho (Frontiers in Psychiatry, 2022)
Background: This study investigated the associations of sleep disturbance and serum serotonin levels with suicidal ideation, and evaluated the potential modifying effects of serotonin on these associations in patients with acute coronary syndrome (ACS). Methods: In total, 969 ACS patients were recruited from a tertiary university hospital in Korea within 2 weeks of disease onset and evaluated in terms of sleep disturbance (using the Leeds Sleep Evaluation Questionnaire), serum serotonin levels, and suicidal ideation (using the “suicidal thoughts” item of the Montgomery–Åsberg Depression Rating Scale). Covariates included sociodemographics, depression, vascular risk factors, and disease severity. After 1 year, 711 patients were re-evaluated in terms of suicidal ideation. Logistic regression analysis was performed with adjustment for covariates. Results: Sleep disturbance was significantly associated with suicidal ideation at baseline and follow-up. Serum serotonin showed no such association, but modified the association of sleep disturbance with suicidal ideation such that it was significant only in the lower serum serotonin group, with significant interaction terms obtained after adjustment for relevant covariates. Conclusions: Evaluating sleep disturbance and serum serotonin levels could improve the accuracy of clinical predictions of suicidal ideation in the acute and chronic phases of ACS.